OP0161 ASSOCIATION OF BASELINE CYTOTOXIC GENE EXPRESSION WITH USTEKINUMAB RESPONSE IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Seridi, L.; Cesaroni, M.; Loza, M. J.; Schreiter, J.; Sweet, K.; Orlovsky, Y.; Baribaud, I.; Orillion, A.; Lipsky, P.; Vollenhoven, R. V.; Hahn, B. H.; Tsokos, G.; et al.
Abstract : Background: Systemic Lupus Erythematous (SLE) is a clinically and biologically diverse disease, for which only one new therapy has been approved in the past 60 years. In a phase 2 trial on patients with mild-to-moderate SLE, ustekinumab (UST) improved clinical and laboratory measures of disease activity compared with placebo (PBO). 1 Objectives: We previously reported an association of IFN-γ reduction with response to UST, 2 suggesting an impact on the IL12/Th1 axis. To extend these findings, we performed unbiased transcriptomic analysis from baseline whole blood samples to identify genes that discriminate UST responders (UST-R) from non-responders (UST-NR) using the primary endpoint of Systemic Lupus Erythematosus Responder Index (SRI)-4 at week 24 to define response. Methods: UST was studied in a Ph2 PBO-controlled study of 102 patients with seropositive SLE and active disease despite standard therapy. Patients were randomized 3:2 to receive IV UST 6 mg/kg or placebo followed by subcutaneous injections of UST 90 mg or PBO every 8 weeks. Whole blood gene expression at baseline was measured via microarray using RNA samples from 100 patients, as samples from 2 patients failed quality control. An unbiased approach was used to identify gene signatures present at baseline that associate with UST response. Recombinant IL-12 or IL-23 was incubated in vitro with whole blood from 6 healthy donors for 24h and RNA-Seq was performed to determine the effect of these treatments on representative genes comprising the UST response signature. Results: A non-biased machine learning algorithm identified a 9-gene whole blood signature composed primarily of cytotoxic cell-associated transcripts (PRF1, KLRD1, GZMH, NKG7, GNLY, FGFBP2, TRGC2, TARP, TRGV2) that was enriched at baseline in UST-R vs UST-NR. By Gene Set Variation Analysis, the cytotoxic signature enrichment in UST-NR was less at baseline than both UST-R and a healthy control cohort (P=0.0087, P=0.056, respectively), whereas UST-R cytotoxic gene enrichment was similar to healthy controls (P=0.31). No significant difference in cytotoxic signature enrichment was observed at baseline between PBO responders and PBO non-responders or healthy controls (Figure). Enrichment levels of the cytotoxic gene signature remained stable over time in PBO and UST-NR groups while a trend of decreased cytotoxic signature was observed in UST-R, although never reaching levels seen in UST-NR. To begin to understand the relationship between IL-12 and IL-23, the targets of UST, and the cytotoxic signature, whole blood was stimulated with these cytokines in vitro . Recombinant IL-12, but not IL-23, resulted in increased expression of representative members of this cytotoxic gene signature. Conclusion: We identified a novel cytotoxic signature in baseline blood samples that associated with UST response in SLE. The observation that IL-12 can increase this signature in vitro and that IL-12 is a robust inducer of cytotoxic cell activity 3 as well as IFN-γ 3 suggests an important role of IL-12 blockade in the mechanism of action of UST in SLE. References: [1]van Vollenhoven RF. Lancet. 2018;392:1330-39 [2]Jordan. ACR 2018 Abstract # 2951 [3]G. Trinchieri. Nat Rev Immunol. 2003;3:133-46 Disclosure of Interests: Loqmane Seridi Employee of: Janssen Research & Development, LLC, Matteo Cesaroni Employee of: Janssen Research & Development, LLC, Matthew J Loza Employee of: Janssen Research & Development, LLC, Jessica Schreiter Employee of: Janssen Research & Development, LLC, Kristen Sweet Employee of: Janssen Research & Development, LLC, Yevgeniya Orlovsky Employee of: Janssen Research & Development, LLC, Spring House, PA, United States of America, Isabelle Baribaud Employee of: Janssen Research & Development, LLC, Ashley Orillion Employee of: Janssen Research & Development, LLC, Peter Lipsky Consultant of: Horizon Therapeutics, Ronald van Vollenhoven Grant/research support from: AbbVie, Amgen, Arthrogen, Bristol-Myers Squibb, GlaxoSmithKline (GSK), Janssen Research & Development, LLC, Lilly, Pfizer, Roche, and UCB, Consultant of: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, GSK, Janssen, Lilly, Medac, Merck, Novartis, Pfizer, Roche, UCB and Vertex, Speakers bureau: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, Crescendo Bioscience, GlaxoSmithKline, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, UCB, Vertex, Bevra H. Hahn Grant/research support from: Janssen Research & Development, LLC, George Tsokos Grant/research support from: Janssen Research & Development, LLC, Marc Chevrier Employee of: Janssen Research & Development, LLC, Shawn Rose Employee of: Janssen Research & Development, LLC, Frederic Baribaud Shareholder of: Janssen Research & Development, LLC, Employee of: Janssen Research & Development, LLC, Jarrat Jordan Employee of: Janssen Research & Development, LLC